Analysis of the Factors Influencing Inflationary Dynamics in Nepal - Joshi, Purnanand (NPRC Journal of Multidisciplinary Research, 2026)
Background: Inflation in Nepal has remained high and volatile, exceeding levels considered optimal for sustained economic growth. While existing studies have primarily focused on traditional domestic economic factors, Nepal’s growing integration with the global economy and its history of political and economic shocks suggest that external and non-economic factors may also significantly influence its inflationary dynamics. This study addresses this research gap by investigating a broader set of potential determinants. Objectives: The primary objective of this study is to analyze the impact of both economic and non-economic factors on inflation in Nepal. It specifically aims to assess the roles of money supply, fiscal deficit, trade openness, India’s wholesale price index (WPI), the output gap, the policy shift to liberalization, and periods of unusual circumstances. Methods: The study employs an Auto-Regressive Distributed Lag (ARDL) bounds testing approach to cointegration using annual time-series data from 1975 to 2022. Dummy variables are incorporated to capture the effects of the post-1990 liberalization policy regime (D1) and unusual circumstances such as conflict and natural disasters (D2). Diagnostic and stability tests ensure the robustness of the model. Findings: The results confirm a long-run cointegrating relationship among the variables. In the long run, money supply, trade openness, and India’s WPI have a significant positive impact on inflation in Nepal. The shift to a liberalization policy regime is associated with a significant reduction in inflation. Conversely, the fiscal deficit, output gap, and dummy for unusual circumstances are found to be statistically insignificant in explaining inflationary trends. Conclusion: Inflation in Nepal is determined by a mix of internal monetary factors, external trade-linked factors, and policy regime changes. Monetary policy remains essential for price stability. To curb imported inflation and enhance resilience, policies should focus on boosting domestic productive capacity through import substitution, trade diversification, and fostering a stable investment climate. Novelty: This study contributes to the literature by being among the first in the Nepalese context to empirically incorporate and test the impact of trade openness, the output gap, and qualitative non-economic factors (policy regime change and unusual circumstances) within a unified ARDL framework, moving beyond the conventional analysis of traditional variables.